Effect of Dietary Energy and Protein on Performance, Egg Composition, Egg Solids, Egg Quality and Profits of Hy-Line W-36 Hens During Phase 2 - Wu, Guangbing; Gunawardana, P.; Bryant, M.M.; Roland, Sr., D.A. (International Journal of Poultry Science, 2007)
A 4×3 factorial experiment with four added dietary energy (fat) levels (0.00 (0.00), 0.33 (16.7), 0.67 (33.5) and 1.00 (50.4) MJ ME/kg (g fat/kg)) and three protein levels (173.9, 166.5 and 160.7 g protein/kg) was conducted to determine the effect of dietary energy on performance, egg composition, egg solids, egg quality and profits of Hy-line W-36 hens at different protein levels. Hy-line W-36 hens (n = 1080) in Phase II (40 weeks of age) were randomly divided into 12 treatments (6 replicates of 15 birds per treatment) and fed the experimental diets for 12 wks. There was no significant interaction on all parameters between dietary energy and protein. Increasing protein had a significant effect on nutrient intake per g egg, percent albumen and yolk/albumen ratio, but had no effect on performance, egg solids, or egg quality. Hens had the capability to linearly decrease feed intake as dietary energy level increased so that the similar quantities of dietary energy (0.022 to 0.023 MJ/kg) was consumed to produce 1 g egg. Increasing dietary energy by the addition of poultry oil significantly improved nutrient (protein, lysine, or TSAA) utilization. As added dietary energy increased from 0.00 to 0.67 MJ/kg, feed intake linearly decreased and feed conversion linearly improved. However, a further increase of added dietary energy from 0.67 to 1.00 MJ/kg had no additional effect on feed intake and feed conversion. Based on feed intake and feed conversion, increasing 0.67 MJ/kg dietary energy by the addition of 33.5 g poultry oil/kg gave optimal performance in Hy-line W-36 hens from 40 to 51 wk of age. Because feed ingredient prices and egg price vary, there can be no fixed ideal dietary energy level for optimal profits during phase 2 (wk 40 to 51).